1996
DOI: 10.1002/j.1460-2075.1996.tb00424.x
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of poly(A) binding protein prevents maturation-specific deadenylation and translational inactivation in Xenopus oocytes.

Abstract: The translational regulation of maternal mRNAs is the primary mechanism by which stage‐specific programs of protein synthesis are executed during early development. Translation of a variety of maternal mRNAs requires either the maintenance or cytoplasmic elongation of a 3′ poly(A) tail. Conversely, deadenylation results in translational inactivation. Although its precise function remains to be elucidated, the highly conserved poly(A) binding protein I (PABP) mediates poly(A)‐dependent events in translation ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
92
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(98 citation statements)
references
References 62 publications
5
92
1
Order By: Relevance
“…Thus, cytoplasmic polyadenylation is thought to exert its effects on translation largely by recruiting PABPs to the newly extended poly(A) tails. Consistent with a role of PABP in poly(A) tail mediated changes during oogenesis, overexpression of PABP1 in X. laevis oocytes blocks the maturation-induced deadenylation and translational inactivation of mRNAs that lack CPEs, as well as inhibiting the recruitment of some CPE-containing mRNAs onto polysomes (Wormington et al 1996). A role for PABP in oogenesis is also indicated by early meiotic defects in PAB-1-deficient C. elegans (Maciejowski et al 2005).…”
Section: Pabpssupporting
confidence: 52%
“…Thus, cytoplasmic polyadenylation is thought to exert its effects on translation largely by recruiting PABPs to the newly extended poly(A) tails. Consistent with a role of PABP in poly(A) tail mediated changes during oogenesis, overexpression of PABP1 in X. laevis oocytes blocks the maturation-induced deadenylation and translational inactivation of mRNAs that lack CPEs, as well as inhibiting the recruitment of some CPE-containing mRNAs onto polysomes (Wormington et al 1996). A role for PABP in oogenesis is also indicated by early meiotic defects in PAB-1-deficient C. elegans (Maciejowski et al 2005).…”
Section: Pabpssupporting
confidence: 52%
“…Overexpression of PABP leads to defects in cell division of the fission yeast Saccharomyces pombe (Tallada et al, 2002) and increases the translation termination efficiency in Saccharomyces cerevisiae (Cosson et al, 2002). Moreover, high PABP levels interfere with maturation-specific deadenylation and translational inactivation of maternal mRNAs in Xenopus oocytes (Wormington et al, 1996). In addition, elevated PABP levels have been detected in early stages of cancer supporting a link between cell growth and PABP levels (Verlaet et al, 2001).…”
Section: Discussionmentioning
confidence: 98%
“…In Spisula embryogenesis, PABP is somehow masked in maturing oocytes and unable to bind polyadenylated RNA, revealing the existence of regulatory mechanisms operating on this class of proteins (de Melo Neto et al 2000). Accordingly, PABP overexpression prevented maturation-dependent deadenylation and translation inactivation of maternal transcripts but did not interfere with CPE-mediated polyadenylation (Wormington et al 1996). Since ePABP is replaced by increasing levels of PABP in later stages of development after zygotic gene activation (Voeltz et al 2001;Seli et al 2005), this programmed substitution of the universal translation effector is likely pivotal for guiding further specifi- (Mendez and Richter 2001), ePABP/PABP1 (Seli et al 2005), DAZL (Moore et al 2003;Collier et al 2005), and Pumilio (Wharton et al 1998) are shown.…”
Section: Translation Regulatory Cascades Genes and Development 141mentioning
confidence: 97%
“…The role of the polyadenylation process and resulting poly(A) tail in maternal mRNA gene expression is crucial, dictating either deadenylation or translation (Jackson and Standart 1990; Wormington et al 1996;Richter 1999). Interestingly, there is no decay of Xenopus messages following deadenylation through oocyte maturation or in the early stages of embryo development (until the mid-blastula transition), suggesting a reversible regulatory process that can shift mRNAs between repressed and translationally active states (Audic et al 1997;Voeltz and Steitz 1998).…”
Section: Poly(a)-dependent Translation Controlmentioning
confidence: 99%